Solution:
Given the system of equations:
![\begin{gathered} 2x+y=9\text{ --- equation 1} \\ x+4y=1\text{ ---- equation 2} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/n2ra5045k8xs0p9x5j5j1qug2xb33h9bn9.png)
To solve,
Step 1: From equation 1, solve for y.
To solve for y, we make y the subject of the equation.
Thus,
![\begin{gathered} 2x+y=9 \\ add\text{ -2x to both sides of the equation,} \\ -2x+2x+y=-2x+9 \\ \Rightarrow y=-2x+9\text{ ----- equation 3} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/i8uznsweq04pjb980ab3zkv1m4hs3dp3w7.png)
Step 2: Substitute equation 3 into equation 2, to solve for x.
Thus,
![\begin{gathered} x+4y=1 \\ \Rightarrow x+4(-2x+9)=1 \\ open\text{ parentheses,} \\ x-8x+36=1 \\ \Rightarrow-7x+36=1 \\ subtract\text{ 36 from both sides of the equation,} \\ -7x+36-36=1-36 \\ \Rightarrow-7x=-35 \\ divide\text{ both sides by the coefficient of x, which is -7} \\ -(7x)/(-7)=-(35)/(-7) \\ \Rightarrow x=5 \end{gathered}]()
Step 3: To solve for y, substitute the value of 5 for x into equation 3.
From equation 3,
![\begin{gathered} y=-2x+9 \\ where \\ x=5 \\ thus, \\ y=-2(5)+9=-10+9 \\ \Rightarrow y=-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/adn3lb6xo959zmnsewrq6sux3dfsomza4j.png)
Hence, the step that contains the first error is
![Substitute:The\text{ equation 2x+y=9 becomes 2x+\lparen-2x+9\rparen=9}](https://img.qammunity.org/2023/formulas/mathematics/college/t7lkaiqgcpxr6b67rpummipe81hqnt5x60.png)